Social Brain Development in Williams Syndrome: The Current Status and Directions for Future Research - Haas, Brian W.; Reiss, Allan L. (Frontiers in Psychology, 2012)
Williams syndrome (WS) is a neurodevelopmental condition that occurs as a result of a contiguous deletion of ∼26–28 genes on chromosome 7q11.23. WS is often associated with a distinctive social phenotype characterized by an increased affinity toward processing faces, reduced sensitivity to fear related social stimuli and a reduced ability to form concrete social relationships. Understanding the biological mechanisms that underlie the social phenotype in WS may elucidate genetic and neural factors influencing the typical development of the social brain. In this article, we review available studies investigating the social phenotype of WS throughout development and neuroimaging studies investigating brain structure and function as related to social and emotional functioning in this condition. This review makes an important contribution by highlighting several neuro-behavioral mechanisms that may be a cause or a consequence of atypical social development in WS. In particular, we discuss how distinctive social behaviors in WS may be associated with alterations or delays in the cortical representation of faces, connectivity within the ventral stream, structure and function of the amygdala and how long- and short-range connections develop within the brain. We integrate research on typical brain development and from existing behavioral and neuroimaging research on WS. We conclude with a discussion of how genetic and environmental factors might interact to influence social brain development in WS and how future neuroimaging and behavioral research can further elucidate social brain development in WS. Lastly, we describe how ongoing studies may translate to improved social developmental outcomes for individuals with WS.